Efforts on Developing Sustainable Production of Surakarta’s Tiga Negeri Batik from Handmade Technique to Cold Wax Technique. - Apika Nurani Sulistyati; Theresia Widyastuti (Javanologi: International Journal of Javanese Studies, 2023)
A piece of batik cloth contains philosophical values, symbolic meanings, traces of events, ethnic identity, social stratification, spirituality, and records of the journey of civilization. Tiga Negeri batik is evidence of cultural assimilation and acculturation in Java. Tiga Negeri is the nickname for the three places from which batik is made from the process of designing, drawing (mbatik), and onto coloring. This batik, which is closely related to Chinese culture, originated in Lasem, then during its spread to Surakarta, the motifs and color schemes became richer due to the assimilation between coastal batik and inland batik, and thus it eventually became Tiga Negeri batik from Surakarta. However, recently this unique Surakarta’s Tiga Negeri batik is losing its prestige and requires revitalization efforts to sustain its sustainability.